Multi-device digital assistance - White, Ryen W.; Fourney, Adam; Herring, Allen; Bennett, Paul; Chandrasekaran, Nirupama; Sim, Robert; Nouri, Elnaz; Encarnación, Mark (Communications of the ACM, 2019)
Increased availability of cloud services and ownership of multiple digital devices create unique opportunities for digital assistants to provide guidance across a range of tasks and scenarios.